Masters of disaster : the ten commandments of damage control - Lehane, Christopher. (Palgrave Macmillan, 2012)
Whether you're a politician caught with his pants down, a publicly traded company accused of accounting improprieties, a family-owned restaurant with a lousy Yelp review or just the guy in the corner cubicle who inadvertently pushed "reply all," a crisis doesn't have to be the make-or-break moment of your career. For those of us that aren't natural spin doctors, it's hard to resist the impulse to cover your tracks, lie, or act like nothing happened. But resist you must. Full of both lively personal anecdotes and hard-knuckled straight talk, this is a must-read for anyone who wants to emerge with their reputation intact.